Lagenandra pradeepiana, a new species of aroid from Western Ghats, India - Pushkaran, Pooja; Venugopal, Mithun; Narayanan, Matalayi Kokarambath Ratheesh; Sunil, Chandrasseril Narayanan (Phytotaxa, 2025)
Lagenandra pradeepiana, a new species of Araceae from Kerala, India is described and illustrated in photographs. It is closely allied to L. ovata, which shares characteristics such as scarce fibrous roots and a semi-circular petiole. However, it differs primarily in having a significantly long peduncle, distinct colour zones in the spathe, and a spadix with a well-developed, tapering appendix. The species also resembles L. toxicaria var. barnesii in its oblique leaf base and tapering spadix appendage but differs in having leaves with scalloped margins, a longer peduncle, and more ovules without placental hairs. A detailed morphological comparison with allied taxa and information on its distribution and conservation status are provided. The species has been classified as Critically Endangered according to the IUCN Red List, specifically under Criterion CR B1ab (ii, iii, iv, v) +2ab (ii, iii, iv, v).